The Role of Applied Linguistics in English Teaching Materials in Higher Education - Abd. Syakur (BIRCU, 2021)
The goal of this research was to find out what role linguistics plays in the English teaching process that takes place at Bakti Indonesia University. The lecturer of Bakti Indonesia University, teaching English along with technological developments can be implemented with various methods and development efforts. One of the efforts made was to optimize the linguistics role, especially applied linguistics, in English teaching process. It is very natural in English teaching process as broad knowledge which is fundamental about the principles of language being learned. The linguistic theories of English lecturers and teaching staff will not find any problems in describing a language especially English in its use. The research method used was descriptive with qualitative approach in its implementation. From the results can be concluded that the teaching method of English language material is not only learning system that plays major role, but more than that it is communication medium that can understand the basic principles of English teaching. For a student that learning any language requires a lot of process and practice in English.